2005
DOI: 10.1021/jp0542975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Electron−Alkali Cation Pairs in Bulk Water

Abstract: The structural, dynamic, and thermodynamic properties of an excess electron interacting with an alkali cation (Na+, K+, Li+) in bulk water were investigated by means of a mixed quantum-classical molecular dynamics simulation technique. This study includes a reparametrization of the electron-cation pseudopotentials. The free energy calculations for all three systems show that a contact electron-cation pair can be observed, which is either as stable as the dissociated pair (Li+) or more stable by only a few kT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…This implies that aqueous solutions of alkali cations and hydrated electrons should exhibit a statistical distribution of species rather than specifically forming contact pairs. 12 This previous work is suggestive, but to the best of our knowledge, there has been no simulation work targeted at experimentally realizable alkali cation-electron tight-contact pairs, such as the alkali atoms in liquid ethers.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that aqueous solutions of alkali cations and hydrated electrons should exhibit a statistical distribution of species rather than specifically forming contact pairs. 12 This previous work is suggestive, but to the best of our knowledge, there has been no simulation work targeted at experimentally realizable alkali cation-electron tight-contact pairs, such as the alkali atoms in liquid ethers.…”
Section: Introductionmentioning
confidence: 99%
“…Boutin and co-workers accomplished this with a perturbation-theorybased method, 26 and they found that the PMF consists of a well that is ∼5 k B T deep with an energetic minimum located at an e − −Na + distance of ∼2 Å: in other words, they found that Na + forms a stable contact pair with the hydrated electron. 17 Boutin and co-workers then went on to examine how the absorption spectrum of the MQC-simulated hydrated electron varies as a function of distance from the Na + cation. They found that proximity to a sodium cation indeed led to a blueshift of the electron's calculated spectrum and that the magnitude of the spectral shift varied roughly inversely with the sodium−electron distance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…14 Boutin and co-workers' MQC simulations, however, found that the hydrated electron's spectrum changed shape quite a bit when in a contact pair with a sodium cation. 15,17 Finally, when Boutin and co-workers attempted to mimic the concentration dependence of the electron's spectrum by varying the electron−cation distance, 17 the spectral behavior had a different dependence than that seen experimentally. 14 These discrepancies mean that something in the MQC simulations is not capturing the correct experimental behavior.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We report here mixed quantum-classical simulations (QCMD), successfully used to better understand the solvated electron-cations interactions in bulk water, [17,18] applied to the study of the solvated electron in water confined in the pores of a siliceous faujasite. A schematic view of a faujasite supercage is represented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%